Könnyű leckék - Zurbó, Dorottya; Ugrin, Julianna; Sass, Péter; Pavlovskaya, Natasha; Várhegyi, Rudolf H.A.S.E.; Balázs, Ádám (Hungary : ELF Pictures, 2018)
Kafia, at the age of fifteen, escaped from a child marriage in Somalia and came to Hungary, where she lived in a state orphanage in Budapest. Two years later, she is preparing for graduation exams and trying a career in modelling. Everything seems fine on the surface, but her beautiful and confident appearance conceals anxieties and doubts about leaving behind her mother, her culture, and everything she grew up with. As she becomes more comfortable with the camera, the film slowly becomes an intimate confession. What does it mean to break with your past and give yourself up to a new self—one on the brink of adulthood?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films